Design, Synthesis and Anticancer Activity of Benzothiazole Hybrids: Insights from Molecular Docking Studies - Kotte, Raju; Vedula, Girija Sastry (Asian Journal of Chemistry, 2025)
A series of benzothiazole hybrids 5a-n bearing acetamide and benzamide functionalities were synthesized and evaluated for their anticancer activity and binding affinity with epidermal growth factor receptor (EGFR) targets, 4WKQ and 6LUD. The synthesis involved the synthesis of 6-hydroxy-2-aminobenzothiazole, followed by methylation and coupling with carboxylic acids to yield benzothiazole hybrid compounds. The structures of the synthesized compounds were confirmed using analytical techniques such as 1H NMR, 13C NMR and HRMS techniques. Molecular docking studies indicated that the hydroxyl (-OH) and amino (-NH2) groups significantly enhanced binding to both EGFR targets, with compounds 5j (3-OH) and 5i (4-OH) showing the highest binding affinities. The anticancer activity of these hybrids was tested against MCF-7 breast cancer, HCT-116 colon cancer and HEK-293 normal cells using MTT assays. The compounds exhibited promising cytotoxicity, with meta-substituted derivatives showing superior activity. Among them, compounds 5f, 5h, 5i, 5j and 5m demonstrated a significant potency, suggesting their potential as candidates for further development in cancer research.